2018
DOI: 10.1093/milmed/usx125
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Prophylaxis with Combat-Related Open Soft-Tissue Injuries

Abstract: Use of non-guideline directed EGN-based post-trauma antibiotic prophylaxis does not improve infectious outcomes nor does it shorten hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Lloyd et al, in 2018 [ 37 ], considered the effect of antibiotic prophylaxis in combat-related open soft tissues wounds in a retrospective study based on 287 patients. The study compared infectious outcomes in narrow prophylaxis regimens (as indicated by Department of Defense guidelines) and expanded gram negative coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Lloyd et al, in 2018 [ 37 ], considered the effect of antibiotic prophylaxis in combat-related open soft tissues wounds in a retrospective study based on 287 patients. The study compared infectious outcomes in narrow prophylaxis regimens (as indicated by Department of Defense guidelines) and expanded gram negative coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Broad spectrum AP in open skin and soft tissue combat-related injuries is necessary and beneficial to decrease infection rates and length of hospital stay. 126,127 Data on skin and soft tissue injuries reported a synergistic effect of extensive wound irrigation and AP in decreasing the incidence of infection in moderately and severely contaminated skin and soft tissue injuries. 128 The reported different rates of infections in different management strategies include 17% in irrigation/no AP, 40% in AP/no irrigation, and 75% in no AP/no irrigation group ( p < 0.0005).…”
Section: Thoracic Traumamentioning
confidence: 99%
“…The need for AP, often suggested and used by physicians, needs to be assessed. Broad spectrum AP in open skin and soft tissue combat-related injuries is necessary and beneficial to decrease infection rates and length of hospital stay 126,127 . Data on skin and soft tissue injuries reported a synergistic effect of extensive wound irrigation and AP in decreasing the incidence of infection in moderately and severely contaminated skin and soft tissue injuries 128 .…”
Section: Definitionsmentioning
confidence: 99%
“…The rule of thumb here is to administer antibiotics as soon as possible. In case of any delay, they can be administered up to 3 hours after injury but not later than 6 hours after injury (2,(33)(34)(35).…”
Section: Medication Prophylaxis and Antibiotic Treatmentsmentioning
confidence: 99%